WILAYAH MINANGKABAU DALAM PANTUN ADAT MINANGKABAU KARYA N.M. RANGKOTO - Noviyola, Dwi Sita; Wulandari, Yosi (Jurnal Tradisi Lisan Nusantara, 2024)
The background of this research is the division of the Minangkabau area in the Minangkabau tra-ditional pantun which will then be analyzed for its meaning based on the study of Paul Ricoure's Hermeneutics. This study aims to: describe the Minangkabau territorial division system in the Pantun Adat Minangkabau by N.M. Ragkoto. This type of research uses a qualitative descriptive research type. The data collection method used is the observing method and the note taking tech-nique. Data analysis techniques were carried out using descriptive qualitative analysis techniques with the study of Paul Ricoure's Hermeneutics. The research results obtained are as follows. Minangkabau territorial divisions in the book Pantun Adat Minangkabau by N.M. Rangkoto found six pantun data using Paul Ricoure's Hermeneutics study. The six rhymes are Luhak dan Rantau, Luhak Nan Tigo, Lareh Nan Duo, Nagari, Taratak Dusun and Koto, Luhak Agam. The Minangkabau area is divided into three, namely darek, rantau, and coast. Many darek and rantau areas are found, but for coastal areas they are not found because these areas are only described in Minangkabau customary taboos.